2016
DOI: 10.1016/j.watres.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment as development and decision support tool for wastewater resource recovery technology

Abstract: Life cycle assessment (LCA) has been increasingly used in the field of wastewater treatment where the focus has been to identify environmental trade-offs of current technologies. In a novel approach, we use LCA to support early stage research and development of a biochemical system for wastewater resource recovery. The freshwater and nutrient content of wastewater are recognized as potential valuable resources that can be recovered for beneficial reuse. Both recovery and reuse are intended to address existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 55 publications
4
43
0
2
Order By: Relevance
“…It was mainly due to the NH3 air emissions derived from NH4+ volatilization in HRAPs and to the heavy metals content in the digestate/biofertilizer (emissions to soil). The results are consistent with previous studies that reported increased toxicity in a comparative LCA by integrating a sidestream process into a conventional wastewater treatment facility where microalgae are cultivated, harvested and then used for fertigation (Fang et al, 2016). Furthermore, it was observed that the higher impacts on terrestrial environments are unavoidable in cases where sludge and nutrients from wastewater are recycled and reused in agriculture (Tangsubkul et al, 2005).…”
Section: Climate Change Ozone Depletion Photochemical Oxidant Formasupporting
confidence: 92%
See 1 more Smart Citation
“…It was mainly due to the NH3 air emissions derived from NH4+ volatilization in HRAPs and to the heavy metals content in the digestate/biofertilizer (emissions to soil). The results are consistent with previous studies that reported increased toxicity in a comparative LCA by integrating a sidestream process into a conventional wastewater treatment facility where microalgae are cultivated, harvested and then used for fertigation (Fang et al, 2016). Furthermore, it was observed that the higher impacts on terrestrial environments are unavoidable in cases where sludge and nutrients from wastewater are recycled and reused in agriculture (Tangsubkul et al, 2005).…”
Section: Climate Change Ozone Depletion Photochemical Oxidant Formasupporting
confidence: 92%
“…Depletion, Human Toxicity and Terrestrial Ecotoxicity. These impact categories were selected according to the most relevant environmental issues related to wastewater treatment and used in previous LCA studies (Corominas et al, 2013;Fang et al, 2016;Gallego et al, 2008;Garfí et al, 2017;Hospido et al, 2008). Normalisation was carried out in order to compare all the environmental impacts at the same scale.…”
Section: Photochemical Oxidant Formation Particulate Matter Formatiomentioning
confidence: 99%
“…The topics of food production (n = 4), mobility (n = 2), and biomass production (n = 1) are analyzed as well. Most authors concluded that applying prospective LCA is useful, leads to new insights during the development of new technologies, and can support policymakers in their work [25,26,32,[34][35][36][37]. Zimmermann et al [27] expand this argument in concluding that prospective LCAs lead to a more robust analysis than traditional static LCAs.…”
Section: Resultsmentioning
confidence: 99%
“…algal biomass) and poor in soluble inorganic nutrients -a medium aimed to be used for fertigation (11). The effluent produced by the TRENS system should be harmless to the environment.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction of influent nitrogen which cannot be recovered via algal cultivation is removed via the completely autotrophic nitrogen removal (CANR) process. TRENS has been demonstrated to be more sustainable than conventional wastewater treatment based on chemical dosing (11).…”
Section: Introductionmentioning
confidence: 99%